Anti-Müllerian hormone in serum and seminal plasma in comparison with other male fertility parameters. (3rd May 2016) - Kucera, Radek; Ulcova-Gallova, Zdenka; Windrichova, Jindra; Losan, Petr; Topolcan, Ondrej
ABSTRACT: Anti-Müllerian hormone (AMH) is a factor most associated with female fertility and especially with the ovarian reserve. AMH is also used as a parameter of fertility in men as it arises from the epithelium of the seminiferous tubules that contain Sertoli cells which produce the AMH. To investigate the relationship between AMH production and sperm related parameters we compared the AMH levels in serum and seminal plasma between a group of healthy males ( n =65) and male patients ( n =68) of infertile couples with semen pathology. We assessed the following fertility parameters: sperm count (SC), presence of intra-acrosomal enzymes (IAE), and antispermatozoal antibodies (ASA). Infertile men were divided into four subgroups according to: SC less than 15 million, SC less than 15 million and lack of IAE, SC less than 15 million and presence of ASA, presence of all three pathological parameters. The mean AMH serum level in the healthy group was 6.95 ng/ml and no significant difference was observed in serum AMH levels. The mean AMH seminal plasma level in the healthy group was 14.21 ng/ml. We observed a statistically significant decrease in the group with a SC with less than 15 million (3.29 ng/ml, p =0.0001) sperm, in the group with SC less than 15 million sperm and lack of IAE (3.95 ng/ml, p =0.0046), and in the group with all three pathological parameters (2.65 ng/ml, p =<0.0001). No significant difference was observed in the group with SC less than 15 million sperm and ASA positivity (11.41 ng/ml, p =0.3171). In conclusion AMH serum levels do not correlate with any of the observed parameters. AMH levels in seminal plasma positively correlate with the pathological SC and with SC pathology and IAE together.